Ítélkezési állandók és vitás kérdések az erkölcsi kártérítés újabb magyar joggyakorlatában - Fézer, Tamás (Debreceni Jogi Műhely, 2004)
Since 1992, date of Constitutional Court’s decision No. 34/1992, certain rules cannot be found in Hungarian Civil Code. There is only a part of a sentence that gives right to any injured person to claim damages in case of personal injuries. More than 10 years after the cassation we are able to look through the legal practice in connection with damages for non-pecuniary loss. The recent re-codifying process plans a brand new institution to substitute and follow damages for non pecuniary loss: pain award. To establish a decent regulation of pain award, jurisdiction of the last decade cannot be neglected. This essay aims to gather typical and crystallized methods of judgements in certain cases, which could be seen as essential and accepted unwritten rules of jurisdiction concerning this field of damages. One of the most difficult problems to solve is the question of amount. This field of damages for non-pecuniary loss is always problematic, because all of the cases are different. Although there are similarities between cases if we examine just damages themselves, but due to the difference of human personality it is almost impossible to give exact phrases and rules to help our judges. We can say that highest amounts are generated by assaults against physical integrity and life. Examination during a legal procedure concentrates on the stress caused by the injury, number of injured rights, age of the injured person and the durability of the harm. If the injured person contributed to the injury, it generates reduced amount of damages. Method of compensation is really simple for the first time. Hungarian legal system knows two different types for the method of damages: in kind or in money. Former one is inapplicable for non-pecuniary losses. If we compensate in money, there are two solutions: injured person can get the whole sum immediately or we can choose allowance as well. The adaptation of allowance is rather small in Hungary, in spite of the advantages this legal institution could offer. It does not mean res iudicata, so it is flexible and offers opportunity to adjust to changed circumstances in the future: both duration and amount of allowance could be changed. It is an interesting question whether personal circumstances of the misdoer could be examined when calculating the amount of allowance. The answer is not unambiguous. Civil law focuses on compensation for the injured party, not the punishment of the misdoer. In spite of this essential lemma, it is necessary to take into account the solvency of the defendant, if we want the plaintiff to get the adjudged amount really. Youth is not the only reason of allowance, sometimes old age could be a well-based legal ground for application of this method of compensation as well. It is really important to examine the personal circumstances of the injured party to choose between these two methods: which one serves the aim of compensation, moderation of lost joy of life the most. Civil Code precludes the possibility to apply both methods together for the same plaintiff. In my opinion the solution of German Civil Code (BGB) should be considered. BGB allows both methods together. It means that possibilities could be wider and fit better to the actual case and its circumstances. Although obligation of damages has two parties traditionally, in a legal procedure of damages for non-pecuniary loss this bipolar situation can be proven false. On the part of the misdoer it is an interesting question what kind of damages can be blamed the state. In Hungary we can meet rules order the responsibility of the state in the field of medical damages or damages for unlawful arrest and illegal imprisonment. Amounts of damages are the highest in these situations. On the part of the injured person an often argued problem the position of secondary victims’ claims. These claims are always problematic, because personality rights belong closely to the person himself and there is no possibility to inherit them. Hungarian Civil Code admits compensation for relatives only in case of injuring reputation of a dead person. There are several decisions in which courts admit these claims on the ground of their sui generis base. It is a decent solution, but because of the uneven jurisdiction it needs codifying. We can say that there are a lot of jurisdictional constants in Hungary in connection with damages for non-pecuniary loss. These are easy to collect and most of them are able to be codified in a strictly non-taxative style. But this examination showed that doubtful questions can also be found in Hungary especially the application of allowance, claims of secondary victims. To arrange these problems, starting point should be jurisdiction itself.